Answers

2014-08-04T17:22:16+08:00
1. *multiply the first equation by two, to cancel the X values: 2(2x - 3y = 5); 4x - 12y = 10; *then add to the second equation: (4x - 12y = 20) + (-4x + 6y = -10) = (-6y = 10) = (y = -5/3); *substitute the value of y in the first equation to get x: [2x - 3(-5/3) = 5] = [2x + 5 = 5] = [x = 0]; 2. *multiply the first equation by two, to cancel the X values: 2(2x + 8y = 3); 4x + 16y = 6; *then add to the second equation: (4x + 16y = 6) + (-4x + 16y = -8) = (32y = -2) = (y = -1/16); *substitute the value of y in the first equation to get x: [2x - 16(-1/16) = 3] = [2x + 1 = 3] = [x = 1];
0
wait.. 2(-3y)= 12y????
Oh yeahm wait. Let me change that
1. *multiply the first equation by two, to cancel the X values: 2(2x - 3y = 5); 4x - 6y = 10; *then add to the second equation: (4x - 6y = 20) + (-4x + 6y = -10) = (0x + 0y = 10) = NO SOLUTION 2. *multiply the first equation by two, to cancel the X values: 2(2x + 8y = 3); 4x + 16y = 6; *then add to the second equation: (4x + 16y = 6) + (-4x + 16y = -8) = (32y = -2) = (y = -1/16); *substitute the value of y in the first equation to get x: [2x - 16(-1/16) = 3] = [2x + 1 = 3] = [x = 1]
woo thank you
You're welcome :)
2014-08-05T00:14:42+08:00